Epidemiology and characteristics of femoral periprosthetic fractures: data from the characteristics, outcomes and management of periprosthetic fracture service evaluation (COMPOSE) cohort study - Baker, P; Gwilym, S; Gacaferi, H (British Editorial Society of Bone and Joint Surgery, 2022)
Aims The aim of this study was to describe the demographic details of patients who sustain a femoral periprosthetic fracture (PPF), the epidemiology of PPFs, PPF characteristics, and the predictors of PPF types in the UK population.